Analisis Pengaruh Digital Marketing Mix Terhadap Keputusan Pembelian Konsumen: Studi Empiris pada Industri E-Commerce di Indonesia - Salhuteru, Andrie Ch.; Hursepuny , Harold (Jurnal Locus Penelitian dan Pengabdian, 2025)
Digital transformation has revolutionized traditional marketing paradigms into digital marketing mix that influences consumer purchasing decisions in e-commerce. This study analyzes the influence of digital marketing mix on consumer purchasing decisions in the Indonesian e-commerce industry. Quantitative methodology with cross-sectional survey design was applied to 2,850 active e-commerce platform consumer respondents from five major Indonesian metropolitan areas. Research instruments utilized structured questionnaires with 5-point Likert scale analyzed through Structural Equation Modeling (SEM). Research findings indicate that digital marketing mix significantly influences purchasing decisions with 74.2% explanatory power. Digital place dimension demonstrates the highest path coefficient (?=0.691), followed by digital product (?=0.624), digital price (?=0.573), and digital promotion (?=0.548). System security emerges as the dominant factor with 0.894 impact index, while customer satisfaction serves as partial mediator (?=0.234). Findings confirm that synergistic integration of digital marketing mix creates holistic ecosystem facilitating purchase conversion optimization within Indonesian e-commerce context.